Kondo temperature of a quantum dot - Nah, Seungjoo (Georgia Institute of Technology, 2011)
The low-energy properties of quantum dot systems are dominated by the Kondo effect. We study the dependence of the characteristic energy scale of the effect, the Kondo temperature, on the gate voltage, which controls the number of electrons in the strongly blockaded dot. We show that in order to obtain the correct Kondo temperature as a function of the gate voltage, it is crucial to take into account the presence of many energy levels in the dot. The dependence turns out to be very different from that in the conventional single-level Anderson impurity model. Unlike in the latter, the Kondo temperature cannot be characterized by a single parameter, such as the ratio of the tunneling-induced width of the energy levels in the dot and the charging energy.